2007
DOI: 10.1159/000103247
|View full text |Cite
|
Sign up to set email alerts
|

Local Therapy of Early Breast Cancer*

Abstract: This review discusses the 2007 St. Gallen oral presentations and posters on the subject of local treatment of primary breast cancer. With a view to surgical interventions, recent results are examined in the management of ductal carcinoma in situ and advanced disease, in sentinel node biopsy and in oncoplastic surgery. In terms of radiotherapy, the focus of this report is on postmastectomy and partial breast irradiation, radiotherapy and systemic therapy, and quality-of-life questions. Finally, conclusions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Tan et al [ 10 ] reported that LVI was significantly associated with SLN macro metastasis. The NSABP B2 trial demonstrated that LVI increases the risk of lymph node involvement in 70-year-old patients with T1 or T2 breast cancer from 10% to 45% [ 26 ]. Our rate of positive LVI (10/13; 77%) in our patients with non-SLN metastasis suggested that LVI was a strong positive predictor of the non-SLN involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [ 10 ] reported that LVI was significantly associated with SLN macro metastasis. The NSABP B2 trial demonstrated that LVI increases the risk of lymph node involvement in 70-year-old patients with T1 or T2 breast cancer from 10% to 45% [ 26 ]. Our rate of positive LVI (10/13; 77%) in our patients with non-SLN metastasis suggested that LVI was a strong positive predictor of the non-SLN involvement.…”
Section: Discussionmentioning
confidence: 99%